ICESat‐2 Constraint Analysis and Monitoring System (CAMS). Issue 5 (12th May 2021) - Rebold, T. W.; Luthcke, S. B.; Pennington, T. A.; Syed, A.; Beall, J. L.; Sabaka, T. J.
Abstract: The Ice, Cloud and land Elevation Satellite‐2 was launched on 15 September 2018 with mission goals of collecting surface elevation data that can precisely measure ice sheet topography, cloud and aerosol heights, land topography, as well as vegetation height for ecosystems studies. The Constraint Analysis and Monitoring System (CAMS) was implemented as an ICESat‐2 ground system element to perform Mission Planning and Spacecraft Safety Monitoring. Mission Planning requires CAMS to serve as an interface between the Project Science Office, the Instrument Support Facility and the Mission Operation Control Center. By ingesting inputs received from all three groups, the CAMS builds an optimized and deconflicted timeline of science and instrument activities. Based upon the timeline of activities, the CAMS utilizes a sophisticated set of algorithms to model and predict the location and pointing of the spacecraft instrument relative to the Earth and Sun. From the predicted position and pointing, the CAMS provides precise monitoring of instrument health, and performs space asset laser conjunction detection. Furthermore, the CAMS determines alternative plans to prevent detected health constraint violations or mitigate potential laser conjunctions. This paper provides an overview of the CAMS and presents the operational performance of planning science and instrument activities, the monitoring of instrument constraints for health and safety, and the space asset laser conjunction screening and mitigation process. Plain Language Summary: The Ice, Cloud and land Elevation Satellite‐2 (ICESat‐2) Constraint Analysis and Monitoring System (CAMS) accurately models and predicts the instrument position and pointing for both Mission Planning and Spacecraft Safety Monitoring. Spacecraft Safety Monitoring involves ensuring the instrument health and safety as well as protecting other space assets in the space environment from being intersected by the ICESat‐2 laser energy (lased). The CAMS accomplishes this by screening the predicted position of known space assets and monitoring instrument health constraints through modeling and prediction. When a health constraint violation is predicted during a spacecraft maneuver, the CAMS performs the analysis necessary to re‐plan the maneuver in order to mitigate the constraint violation. When a laser conjunction has been predicted, the CAMS makes a recommendation to mission operations to perform an avoidance slew or to suspend the firing of the laser until the event has passed. One of the most critical aspects for accurate constraint and lasing event forecasting is the error modeling. The CAMS contains an overall system performance tool which assesses the accuracy of all the system's inputs and outputs. From these performance evaluations the error models can be tuned and continually improved to perform better Spacecraft Safety Monitoring. Key Points: The CAMS is an element of the ICESat‐2 ground system responsible for mission planning and spacecraft safety monitoring Spacecraft safety monitoring includes ICESat‐2 instrument health monitoring and space asset laser conjunction screening The CAMS develops alternative attitude and activity plans to prevent instrument health constraint violations and mitigate laser conjunctions